Valoración económica del servicio de agua y alcantarillado en dos comunidades rurales de la cuenca del Nanay, distrito de San Juan Bautista, 2020 - Saavedra Jarama, Claudio Alejandro (2021)
The subject under study was called "Economic valuation of the water and sewerage service in 2 rural communities of the Nanay basin, District of San Juan. 2020. The objective was to carry out the economic valuation of having the service of treated water and sanitary sewerage in two rural communities of the basin del Nanay, District of San Juan. The non-experimental, quantitative, cross-sectional research design was used. With a simple probabilistic sample, where 84 people who live in the study communities were selected. The results obtained from the surveys were interpreted through descriptive statistics. 72.6% of men and 27.4 of women were interviewed, who have from 1 to 3 children (52.4%) and mostly generate economic income of less than S/: 400.0 (57.1%), they reached grades of primary education (66.66 %) and secondary (33.33%), being their main dedication agriculture (78.6%). They have lived in the area for more than 40 years. They extract water from the river for domestic tasks (81%), the water intended for drinking is previously boiled. They have latrines or rudimentary sanitary booths, whose sewage is often deposited into the environment or underground. Solid waste is deposited in the orchards mostly (69.1%). According to those surveyed, the lack of potable water causes diseases such as diarrhea (the most common), gastrointestinal parasites and typhoid fever. For the study, cases that occurred in the first three months of the study were considered, reporting costs for diarrhea disease (S/.4704.0), parasites (S/.434.0) and typhoid fever (S/.280.0). The calculated costs for illness amount to S/.4.56.0 and the willingness to pay for having drinking water service is S/.9.42.